Perlindungan Hukum Bagi Pihak Ketiga Dalam Perjanjian Fiduciary Security: A Case Study In District Courts - Kadek Aldy Satya Rainartha; I Gusti Ngurah Nyoman Krisnadi Yudiantara (KOLONI, 2024)
This research aims to evaluate the legal protection provided to third parties in fiduciary agreements, with an emphasis on case studies from several district court decisions. In fiduciary agreement schemes, third parties are often caught up in legal disputes between the giver and recipient of the fiduciary. To understand the level of legal protection that exists for third parties, this research uses a normative juridical method with a case study approach to a number of district court decisions in Indonesia. The results of this research reveal that the legal protection available to third parties in fiduciary agreements is still inadequate, especially regarding their rights over fiduciary objects that are used as collateral. This study also found that the application of relevant regulations is often inconsistent, resulting in legal uncertainty for third parties. Therefore, regulatory reform is needed in the field of fiduciary guarantees, as well as increasing legal understanding for all parties involved, including third parties, to ensure that their rights are optimally protected.